Digitization of Religious Tafsir: The Fading of Indonesian Ulama Authority in Post Truth Era - Ichwan, Moh. Nor; Mustaqim Pabbajah; Faizal Amin (UIN Sunan Kalijaga Yogyakarta, 2024)
In the current post-truth era, the traditional authority and credibility of Ulama, who have historically been regarded as the paramount source of religious knowledge, are increasingly compromised. This research investigates the diminishing role and efficacy of Indonesian Ulama in addressing religious and social challenges due to the pervasive influence of the Internet and social media, which provide rapid and seemingly authoritative solutions that overshadow traditional scholarly roles. The study employs a mixed-method approach, integrating observations, interviews, and comprehensive library research, incorporating both physical and digital sources. The findings elucidate three critical issues: first, the limited digital literacy among traditional Indonesian Ulama, which impedes their effective engagement with digital platforms; second, a notable gap in the public's comprehension of how to utilize digital media for religious discourse, despite an increasing interest in religious matters; and third, the superficial understanding and heightened biases among the public, stemming from the ease of accessing religious solutions via social media. This study makes a significant contribution to the discourse by underscoring the urgent necessity for Ulama to enhance their digital literacy, thereby reclaiming their authoritative role in the socio-religious landscape and ensuring that their insights remain relevant and accessible in the digital age.